2013
DOI: 10.3390/md11061899
|View full text |Cite
|
Sign up to set email alerts
|

The Extract of Rhodobacter sphaeroides Inhibits Melanogenesis through the MEK/ERK Signaling Pathway

Abstract: Reducing hyperpigmentation has been a big issue for years. Even though pigmentation is a normal mechanism protecting skin from UV-causing DNA damage and oxidative stress, it is still an aesthetic problem for many people. Bacteria can produce some compounds in response to their environment. These compounds are widely used in cosmetic and pharmaceutical applications. Some probiotics have immunomodulatory activities and modulate the symptoms of several diseases. Previously, we found that the extracts of Rhodobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…One of the extensively investigated transduction mechanisms involved in the melanogenesis process is the MAPKs pathway [42,46]. Previous studies have revealed that phosphorylation of p38 MAPK can induce through activate MITF expression, and also phosphorylation of JNK and ERK can reduce melanogenesis through MITF phosphorylation and its subsequent degradation on B16F10 cells [47][48][49][50][51]. We therefore examined the influence of the purified peptide treatment on the activation of JNK, ERK and p38 MAPK attempting to further understand the molecular mechanisms involved in the pigmentation property of the purified peptide by western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…One of the extensively investigated transduction mechanisms involved in the melanogenesis process is the MAPKs pathway [42,46]. Previous studies have revealed that phosphorylation of p38 MAPK can induce through activate MITF expression, and also phosphorylation of JNK and ERK can reduce melanogenesis through MITF phosphorylation and its subsequent degradation on B16F10 cells [47][48][49][50][51]. We therefore examined the influence of the purified peptide treatment on the activation of JNK, ERK and p38 MAPK attempting to further understand the molecular mechanisms involved in the pigmentation property of the purified peptide by western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the melanin content was analyzed using in situ melanin assay where the cells were dissolved in 1 mol/L NaOH and at high temperature, and the absorbance was read at 450 or 405 nm . Instead, Soluene‐350 was also used to solubilize melanin in cell for melanin quantification . Other methods including oxidation of melanin via alkaline H 2 O 2 which later produced specific markers of black melanin (ie, pyrrole‐2,3,5‐tricarboxylic acid and pyrrole‐2,3‐dicarboxylic acid) and measured using high‐performance liquid chromatography (HPLC) .…”
Section: Protocol and Assaysmentioning
confidence: 99%
“…7,69,126 Instead, Soluene-350 was also used to solubilize melanin in cell for melanin quantification. 16,127 Other methods including oxidation of melanin via alkaline H 2 O 2 which later produced specific markers of black melanin (ie, pyrrole-2,3,5-tricarboxylic acid and pyrrole-2,3-dicarboxylic acid) and measured using high-performance liquid chromatography (HPLC). 16 Recently, re-examination on fluorescence spectroscopy method showed a very high specificity and accuracy for melanin quantification in melanotic cells (ie, melanomas and melanocytes).…”
Section: Assaysmentioning
confidence: 99%
“…Horseradish peroxidase-conjugated secondary antibodies were used, and protein-antibody complexes were visualized using an enhanced chemiluminescence system (Amersham) [14]. The signals were quantified using the ImageJ software (rsbweb.nih.gov/ij/) [15][16][17].…”
Section: Western Blot Analysismentioning
confidence: 99%